Antibacterial modified polypropylene material and preparation method thereof

By introducing the synergistic effect of carbon nanotube-ZnO nanoparticles, chopped carbon fibers and glass fibers into polypropylene materials, and by encapsulating nano-titanium dioxide in chitosan antibacterial microcapsules, the problems of insufficient antibacterial and mechanical properties of polypropylene materials are solved, achieving efficient mechanical reinforcement and long-lasting antibacterial effect.

CN120888138APending Publication Date: 2025-11-04YIWU SHUANGTONG DAILY NECESSITIES CO LTD

Patent Information

Application Number
CN202511156499.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing polypropylene materials have shortcomings in antibacterial properties, especially in the fields of medical and health products and food packaging, where bacteria can easily grow, and conventional modification methods cannot simultaneously improve mechanical properties and antibacterial properties.

Method used

By using carbon nanotubes as a carrier to graft ZnO nanoparticles onto the polypropylene resin interface in a synergistic manner, combined with the "short-range-long-range" synergistic effect of short-cut carbon fibers and glass fibers treated with silane coupling agents, the interfacial compatibility between the nanofiller and the polypropylene matrix is ​​optimized. Furthermore, long-lasting antibacterial effects are achieved by encapsulating hinoki alcohol-loaded nano-titanium dioxide antibacterial microcapsules with chitosan.

Benefits of technology

It significantly improves the mechanical properties and antibacterial activity of modified polypropylene materials, forms a three-dimensional carbon network that runs through the matrix, hinders plastic deformation of the matrix, optimizes stress distribution, and achieves long-lasting antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120888138A_ABST
    Figure CN120888138A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polypropylene, in particular to an antibacterial modified polypropylene material and a preparation method thereof. The problems of poor antibacterial property and mechanical property of the polypropylene material are solved. According to the invention, the carbon nanotube is used as a carrier, ZnO nanoparticles are grafted on the surface, and the carbon nanotube and the polypropylene resin are subjected to interface synergy and functional complementation, so that the mechanical property and antibacterial activity of the material are synchronously improved; through the short-range-long-range synergistic effect of the short carbon fibers and the glass fibers treated by the silane coupling agent KH550, the fracture resistance of the material is remarkably improved; through the molecular-level synergistic effect of hydroxylated boron nitride nanosheets and maleic anhydride grafted polypropylene, the interfacial compatibility of the nanofiller and a polypropylene matrix is optimized, and the mechanical property of the material is improved; the antibacterial microcapsule is prepared by taking chitosan as a carrier, wrapping hinokitiol and loading nano titanium dioxide, and the material is endowed with long-acting antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polypropylene technology, specifically to an antibacterial modified polypropylene material and its preparation method. Background Technology

[0002] In modern industry and daily life, polypropylene (PP), as a commonly used thermoplastic resin, has been widely used in many fields such as packaging, automobile manufacturing, electronics, and medical and health care due to its abundant sources, low price, and good overall performance. However, ordinary polypropylene materials have significant shortcomings, especially in terms of antibacterial properties. In scenarios with stringent hygiene requirements, such as medical and health products and food packaging, bacteria can easily grow and multiply on the surface of polypropylene products. This not only poses a serious threat to product safety but also significantly shortens their service life, greatly limiting the further application and expansion of polypropylene materials. With the booming development of various industries, the performance requirements for polypropylene materials are becoming increasingly stringent, making high-performance polypropylene a focus of market pursuit. High-performance polypropylene not only needs excellent mechanical properties, such as higher strength and toughness, to meet the demands of use in complex environments, but also needs breakthroughs in antibacterial properties. Currently, conventional methods for improving the antibacterial properties of polypropylene, such as blending modification with antibacterial agents and surface treatment, all have certain drawbacks: adding antibacterial agents can easily lead to uneven dispersion and migration, resulting in poor antibacterial durability and potentially damaging the material's mechanical properties; surface treatment processes are complex and costly, and the antibacterial effect cannot penetrate deep into the material, failing to comprehensively meet the demands for high-performance polypropylene.

[0003] To address this, an antibacterial modified polypropylene material and its preparation method are proposed. The resulting modified polypropylene material can be used in automotive interiors. Summary of the Invention

[0004] The purpose of this invention is to provide an antibacterial modified polypropylene material and its preparation method. By using carbon nanotubes as a carrier and grafting ZnO nanoparticles onto the surface, the mechanical properties and antibacterial activity of the material are simultaneously improved through interfacial synergy and functional complementarity with polypropylene resin. The fracture resistance of the material is significantly improved through the "short-range-long-range" synergistic effect of chopped carbon fibers and glass fibers treated with silane coupling agent KH550. The interfacial compatibility between the nanofiller and the polypropylene matrix is ​​optimized through the molecular-level synergistic effect of hydroxylated boron nitride nanosheets and maleic anhydride-grafted polypropylene, thus improving the material's mechanical properties. Antibacterial microcapsules are prepared by using chitosan as a carrier to encapsulate juniper alcohol and loading nano-titanium dioxide, endowing the material with long-lasting antibacterial properties.

[0005] To achieve the above objectives, the present invention provides the following technical solution: It should be noted that all parts in this invention are parts by weight.

[0006] This invention provides a method for preparing an antibacterial modified polypropylene material, the method being as follows: Polypropylene resin and a compatibilizer are premixed at 190°C for 5 minutes to obtain mixture one; chopped carbon fibers, bifunctional fillers, surface-treated glass fibers, hydroxylated boron nitride nanosheets are mixed with a dispersant and ball-milled at 200 rpm for 30 minutes to obtain mixture two; mixture one, mixture two, antibacterial microcapsules, and an antioxidant are added to a twin-screw extruder for melt blending at a screw speed of 500 rpm and a residence time of 5 minutes, followed by extrusion granulation to obtain the modified polypropylene material; The bifunctional filler is carbon nanotubes with ZnO nanoparticles grafted onto their surface; Surface-treated glass fibers are obtained by reacting silane coupling agents with glass fibers; Hydroxylated boron nitride nanosheets were prepared by dispersing boron nitride nanosheets in a sodium hydroxide solution; The antibacterial microcapsules are chitosan encapsulated with juniper alcohol and loaded with nano-titanium dioxide.

[0007] Preferably, the melt index of the polypropylene resin is 10-30 g / 10 min.

[0008] The preferred method for preparing the bifunctional filler is as follows: 10 parts of carbon nanotubes are soaked in 50 parts of mixed acid (concentrated nitric acid: sulfuric acid volume ratio = 1:3) and refluxed at 80℃ for 3-5.5h; then washed until neutral, dispersed in 50 parts of ethanol, and 1.2 parts of 3-aminopropyltriethoxysilane are added, and reacted at 80℃ for 6h to obtain aminated carbon nanotubes; the aminated carbon nanotubes are dispersed in 55 parts of deionized water, 20 parts of 0.1-0.5M zinc nitrate solution are added and stirred for 30min, 1M sodium hydroxide solution is added dropwise until the pH is 10, and stirred at 80℃ for 2h to generate ZnO nanoparticles, then 0.5 parts of polyvinylpyrrolidone are added and stirred for 1h to obtain a reaction solution; the reaction solution is centrifuged, the precipitate is washed 3 times with deionized water, then pre-frozen at -80℃ for 12h, and then dried in a vacuum freeze dryer for 24h to obtain the bifunctional filler.

[0009] Preferred method for preparing antibacterial microcapsules is as follows: 2 parts chitosan are added to 150 parts of 1 wt% glacial acetic acid, stirred at 600 rpm at 40°C until completely dissolved, and impurities are removed by filtering through a 0.45 μm filter membrane to obtain a chitosan solution; 1.2 parts hinoki alcohol and 0.5 parts nano-titanium dioxide are mixed and added to 20 parts anhydrous ethanol, and ultrasonically dispersed for 30 min to obtain a dispersion; the chitosan solution is added and ultrasonically dispersed for another 15-25 min to obtain a mixture; the mixture is then added dropwise to 1… In 60 parts of liquid paraffin, shear emulsification was carried out at 10,000 rpm for 10 min to form an oil-in-water emulsion. 0.15 parts of cystamine were added to the oil-in-water emulsion and stirred at 50°C for 3-5 h to form a dense network structure through cross-linking of chitosan amino groups with cystamine disulfide bonds. 4.25 parts of 2 wt% sodium tripolyphosphate were added and stirred for 30 min. The microcapsule precipitate was then collected by centrifugation and washed three times each with petroleum ether, anhydrous ethanol and deionized water. The microcapsules were then freeze-dried to obtain antibacterial microcapsules.

[0010] Preferably, the average droplet size of the oil-in-water emulsion is 200-500 nm.

[0011] Preferably, the length of the chopped carbon fiber is 50-200 μm.

[0012] Preferably, the surface-treated glass fiber is prepared as follows: 10 parts of glass fiber are immersed in 45 parts of ethanol solution containing 5 wt% silane coupling agent KH550, stirred at 60°C for 2 hours, centrifuged, and dried at 80°C to obtain surface-treated glass fiber; the glass fiber has a diameter of 10 μm and a length of 1-5 mm.

[0013] A preferred method for preparing hydroxylated boron nitride nanosheets is as follows: Sodium hydroxide is dissolved in deionized water to prepare a 3M sodium hydroxide solution; 5 parts of boron nitride nanosheets are added to 100 parts of the sodium hydroxide solution, stirred at 500 rpm for 15 min, and then ultrasonically treated at 60℃ and 300W for 1.8-2.5 h, with nitrogen continuously introduced during the process to obtain a suspension; the suspension is centrifuged at 12000 rpm for 15 min, the supernatant is discarded, deionized water is added, and the mixture is ultrasonically dispersed for 10 min, then centrifuged again. This process is repeated until the pH of the supernatant is 7. After the last centrifugation, the mixture is washed once with anhydrous ethanol, centrifuged at 5000 rpm for 5 min, and then the precipitate after centrifugation is pre-frozen in an ultra-low temperature freezer at -80℃ for 12 h, and then placed in a freeze dryer with a vacuum degree ≤10 Pa and a cold trap temperature of -50℃ for 24 h to obtain hydroxylated boron nitride nanosheets.

[0014] Another aspect of the present invention provides an antibacterial modified polypropylene material, which is prepared by any of the above-mentioned preparation methods; the raw materials for producing the antibacterial modified polypropylene material include 85 parts of polypropylene resin, 1-5 parts of chopped carbon fibers, 3-8 parts of surface-treated glass fibers, 1-3 parts of hydroxylated boron nitride nanosheets, 5-15 parts of antibacterial microcapsules, 1 part of dispersant (zinc stearate: ethylene bis-stearamide mass ratio = 1:1), 0.5-2 parts of compatibilizer (maleic anhydride grafted polypropylene), 3-8 parts of bifunctional filler, and 0.5 parts of antioxidant 1010.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In this invention, the bifunctional filler and polypropylene resin achieve simultaneous improvement in the material's mechanical properties and antibacterial activity through interfacial synergy and functional complementarity. Aminated carbon nanotubes, acting as a maleic anhydride-grafted polypropylene (MAH-g-PP) compatibilizer, form hydrogen bonds and physical entanglements between their surface amino groups and polypropylene molecules, significantly enhancing interfacial bonding and forming a three-dimensional carbon network penetrating the matrix. This effectively transfers stress and hinders plastic deformation of the matrix, significantly improving tensile strength and impact resistance. ZnO nanoparticles are anchored to the carbon nanotube surface, inhibiting matrix crack propagation through the "pinning effect" of the nanoparticles, and also exhibiting antibacterial activity (releasing ZnO). 2+ (Interfering with bacterial metabolism) gives the material antibacterial function.

[0016] 2. In this invention, chopped carbon fibers and glass fibers treated with silane coupling agent KH550 significantly improve the fracture resistance of the material through a synergistic effect of "short-range and long-range". Due to their high modulus, chopped carbon fibers can form micro-reinforcing points within the matrix, absorbing and dispersing local stress. Meanwhile, high aspect ratio glass fibers, through the silane coupling agent and polypropylene compatibilizer, form a strong interfacial bond, exerting a "bridging" effect of continuous fibers and hindering crack propagation paths. The two types of fibers are uniformly distributed during the extrusion process, forming a hierarchical network: carbon fibers primarily focus on micron-scale reinforcement, while glass fibers dominate macroscopic stress bearing. This not only compensates for the interfacial weakness that may be caused by a single fiber but also optimizes stress distribution through the geometric differences between the fibers, ultimately improving the mechanical properties of the material.

[0017] 3. In this invention, the molecular-level synergistic effect of hydroxylated boron nitride nanosheets (OH-BNNS) and maleic anhydride-grafted polypropylene (MAH-g-PP) significantly optimizes the interfacial compatibility between the nanofiller and the polypropylene matrix. The active hydroxyl groups on the surface of OH-BNNS and the anhydride groups of MAH-g-PP are bonded through hydrogen bonds and even partial covalent bonds, solving the aggregation problem caused by the high specific surface area of ​​boron nitride nanosheets and ensuring their uniform dispersion. The nanosheets are inserted into the gaps between polypropylene molecular chains, restricting chain segment movement and significantly improving the rigidity of the matrix. In the preparation process, the dual processes of alkali treatment and ultrasonic exfoliation of boron nitride achieve controllable sheet thickness, while freeze-drying locks in its monolayer dispersion state and avoids secondary aggregation. This linkage strategy of filler pretreatment and compatibilizer addition provides excellent rigidity support for the material.

[0018] 4. In this invention, the antibacterial microcapsules, through the synergistic effect of a dual antibacterial mechanism and a controlled-release process, endow the material with long-lasting antibacterial properties. The cross-linked chitosan network of the shell can dynamically release hinoki alcohol through pH response—in the weakly acidic environment produced by microbial metabolism, the chitosan segments swell and accelerate the release of active ingredients. Hinoki alcohol acts on the bacterial enzyme system and destroys its metabolic capacity, while the coated nano-TiO2 generates reactive oxygen species under light irradiation, achieving environmentally triggered sterilization. In the matrix, the polar chitosan of the microcapsule shell is partially exposed to the matrix surface through a compatibilizer, directionally enriching and contacting pathogenic bacteria, while the hinoki alcohol and TiO2 inside prolong the antibacterial period through a sustained-release mechanism. Attached Figure Description

[0019] Figure 1 The figures show the mechanical property test results of Examples 5, 8-10 and Comparative Examples 7-10 of the present invention. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Please see Figure 1 This invention provides an antibacterial modified polypropylene material and its preparation method, the technical solution of which is as follows: The material information involved in this invention is as follows: 3-Aminopropyltriethoxysilane CAS: 919-30-2; Polyvinylpyrrolidone CAS: 9003-39-8; Chitosan CAS: 9012-76-4; Juniper alcohol CAS: 499-44-5; Liquid paraffin CAS: 8042-47-5; Span 80 CAS: 1338-43-8; Cystamine CAS: 51-85-4; Sodium tripolyphosphate CAS: 7758-29-4; Glass fiber CAS: 65997-17-3; Zinc stearate CAS: 557-05-1; Ethylene bis-stearamide CAS: 110-30-5; Carbon nanotubes were purchased from Shanghai Yi'en Chemical Technology Co., Ltd.; Nano titanium dioxide was purchased from Xuancheng Jingrui New Materials Co., Ltd.; PBS buffer was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; Boron nitride nanosheets were purchased from Zhejiang Yamei Nanotechnology Co., Ltd.; Short-cut carbon fiber was purchased from Jiangsu Chuangyu Carbon Fiber Technology Co., Ltd.; Maleic anhydride-grafted polypropylene was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0022] Example 1

[0023] Ten parts of carbon nanotubes (10 nm in diameter and 20 μm in length) were immersed in 50 parts of mixed acid (concentrated nitric acid: sulfuric acid, volume ratio = 1:3) and refluxed at 80 °C for 3 h to remove impurities and introduce carboxylic acid groups. The mixture was then washed until neutral, dispersed in 50 parts of ethanol, and 1.2 parts of 3-aminopropyltriethoxysilane were added. The mixture was reacted at 80 °C for 6 h to obtain aminated carbon nanotubes. The aminated carbon nanotubes were dispersed in 55 parts of deionized water, and 20 parts of 0.1 M zinc nitrate solution were added and stirred for 30 min. 1 M sodium hydroxide solution was added dropwise until the pH reached 10, and the mixture was stirred at 80 °C for 2 h to allow the OH groups to react. - and Zn 2+ Zn(OH)2 was generated and dehydrated to produce ZnO nanoparticles. Then, 0.5 parts of polyvinylpyrrolidone were added as a stabilizer, and the mixture was stirred for 1 hour to encapsulate the ZnO nanoparticles and inhibit agglomeration, thus obtaining a reaction solution. The reaction solution was centrifuged (8000 rpm, 10 min), and the precipitate was washed three times with deionized water. Then, it was pre-frozen at -80℃ for 12 hours and then dried in a vacuum freeze dryer for 24 hours to obtain a bifunctional filler.

[0024] Ten parts of glass fiber were immersed in 45 parts of ethanol solution containing 5 wt% silane coupling agent KH550, stirred at 60°C for 2 h, centrifuged and dried at 80°C to obtain surface-treated glass fiber; the glass fiber diameter was 10 μm and the length was 1 mm.

[0025] Sodium hydroxide was dissolved in deionized water to prepare a 3M sodium hydroxide solution. Five parts of boron nitride nanosheets were added to 100 parts of sodium hydroxide solution and stirred at 500 rpm for 15 min. Then, the mixture was sonicated at 60℃ and 300W for 1.8 h with nitrogen continuously introduced during the process to obtain a suspension. The suspension was centrifuged at 12000 rpm for 15 min, the supernatant was discarded, and deionized water (twice the original volume each time) was added. The mixture was sonicated for 10 min and centrifuged again. This process was repeated until the pH of the supernatant was 7. After the last centrifugation, the mixture was washed once with anhydrous ethanol to replace the residual water molecules and centrifuged at 5000 rpm for 5 min. The precipitate after centrifugation was then pre-frozen in an ultra-low temperature freezer at -80℃ for 12 h. After that, it was placed in a freeze dryer with a vacuum degree ≤10 Pa and a cold trap temperature of -50℃ and dried for 24 h to obtain hydroxylated boron nitride nanosheets.

[0026] Two parts of chitosan were added to 150 parts of a 1 wt% aqueous solution of glacial acetic acid and stirred at 600 rpm at 40°C until completely dissolved. Impurities were removed by filtering through a 0.45 μm filter to obtain a chitosan solution. 1.2 parts of hinoki alcohol and 0.5 parts of nano-titanium dioxide were mixed and added to 20 parts of anhydrous ethanol. The mixture was ultrasonically dispersed for 30 min (300 W, 40 kHz) to obtain a dispersion. The chitosan solution was then added and ultrasonically dispersed for another 15 min to obtain a mixture. The mixture was then dropwise added to 160 parts of liquid paraffin (containing 1 wt% Span). 80 emulsifier) ​​was used to shear emulsify the mixture at 10,000 rpm for 10 min to form an oil-in-water emulsion with an average droplet size of 200 nm. 0.15 parts of cystamine (dissolved in 10 parts of PBS buffer, pH 7.4) were added to the oil-in-water emulsion, and the mixture was stirred at 50 °C for 3 h to form a dense network structure through cross-linking of chitosan amino groups with cystamine disulfide bonds. 4.25 parts of 2 wt% sodium tripolyphosphate were added and stirred for 30 min. The microcapsule precipitate was then collected by centrifugation (8,000 rpm, 15 min) and washed three times each with petroleum ether, anhydrous ethanol, and deionized water. The microcapsules were then freeze-dried (-50 °C, 48 h) to obtain antibacterial microcapsules.

[0027] Mixture 1 was obtained by premixing 85 parts of polypropylene resin with a melt index of 10 g / 10 min and 0.5 parts of maleic anhydride-grafted polypropylene compatibilizer at 190 °C for 5 min. Mixture 2 was obtained by ball milling 1 part of short-cut carbon fiber with a length of 50 μm, 3 parts of bifunctional filler, 3 parts of surface-treated glass fiber, 1 part of hydroxylated boron nitride nanosheets and 1 part of dispersant (zinc stearate: ethylene bis-stearamide mass ratio = 1:1) at 200 rpm for 30 min. Mixture 2, mixture 1, mixture 2, 5 parts of antibacterial microcapsules and 0.5 parts of antioxidant 1010 were added to a twin-screw extruder for melt blending at a screw speed of 500 rpm and a residence time of 5 min. The mixture was then extruded and granulated to obtain modified polypropylene material. The temperature of the twin-screw extruder was 180 °C in zone 1, 195 °C in zone 2, 205 °C in zone 3, 210 °C in zone 4 and 228 °C at the die head.

[0028] Examples 2-4 The preparation method and parameters of Example 1 are as follows, with specific differences shown in Table 1; the reflux time in Table 1 is the reflux time of carbon nanotubes immersed in mixed acid when preparing bifunctional fillers.

[0029] Table 1 Specific preparation conditions for Examples 2-4

[0030] Comparative Example 1 The preparation method and parameters were the same as in Example 1, except that no bifunctional filler was added.

[0031] Comparative Example 2 The preparation method and parameters of Example 1 are the same, except that aminated carbon nanotubes are used instead of bifunctional fillers.

[0032] Comparative Example 3 The preparation method and parameters of Example 1 are the same, except that the carbon nanotubes were not immersed in mixed acid to introduce carboxylic acid groups when preparing the bifunctional filler.

[0033] Experimental Example 1: Mechanical and Antibacterial Properties Test Tensile properties were tested according to ISO 527; notched impact strength was tested according to ISO 179; with reference to standard QB / T 2591-2003, Escherichia coli was selected as the test strain for antibacterial rate testing; the results are shown in Table 2.

[0034] Table 2 Mechanical and antibacterial properties tests of Examples 1-4 and Comparative Examples 1-3

[0035] As shown in Tables 1 and 2, in Examples 1-4, the bifunctional filler and polypropylene resin, through interfacial synergy and functional complementarity, simultaneously improve the mechanical properties and antibacterial activity of the material. Aminated carbon nanotubes, after being grafted with maleic anhydride and polypropylene compatibilizer, form hydrogen bonds and physical entanglements with polypropylene molecules on their surface, significantly enhancing interfacial bonding and forming a three-dimensional carbon network penetrating the matrix. This effectively transfers stress and hinders plastic deformation of the matrix, significantly improving tensile strength and impact resistance. ZnO nanoparticles are anchored on the surface of carbon nanotubes, inhibiting matrix crack propagation through the "pinning effect" of nanoparticles and imparting antibacterial function to the material due to their antibacterial activity. In Example 2, when the reflux time was 4 h, the zinc nitrate concentration was 0.3 M, the polypropylene resin melt index was 20 g / 10 min, and the bifunctional filler dosage was 5 parts, the resulting material exhibited the best mechanical and antibacterial properties, with a tensile strength of 31 MPa and a notched impact strength of 11.8 kJ / m². 2 The E. coli inhibition rate was 99.5%. In Comparative Example 1, the absence of bifunctional filler resulted in the loss of the synergistic effect of carbon nanotube framework reinforcement and ZnO nanoparticle nanoreinforcement. The polypropylene matrix lacked a three-dimensional network structure formed by CNTs, leading to reduced stress transfer efficiency, unrestricted crack propagation, and decreased mechanical properties. Furthermore, the system without anchored ZnO nanoparticles could not hinder matrix molecular chain slippage through the "pinning effect," weakening the material's rigidity. Additionally, the ZnO nanoparticles released Zn... 2+ The broad-spectrum antibacterial mechanism is lacking, relying solely on antibacterial microcapsules for sterilization, which limits the intensity of action and reduces overall antibacterial efficiency. In Comparative Example 2, aminated carbon nanotubes were used instead of bifunctional fillers. Although aminated CNTs improved the filler-matrix bonding force through interfacial hydrogen bonds, they lacked the nano-reinforcing synergy of ZnO nanoparticles, failing to effectively disperse local stress or inhibit microcrack propagation, resulting in limited improvement in material toughness; moreover, the absence of ZnO caused the material to lose its active antibacterial ability. In Comparative Example 3, the carbon nanotubes were not immersed in mixed acid to introduce carboxylic acid groups during the preparation of the bifunctional filler. Insufficient carboxylic acid groups on the surface of the carbon nanotubes led to incomplete amination reaction, resulting in reduced chemical bonding strength with the MAH-g-PP compatibilizer and weak interfacial bonding force; the filler was prone to agglomeration and could not form an effective three-dimensional network, hindering stress transmission, exacerbating matrix molecular chain slippage, and reducing material strength; insufficient amino loading on the surface of carbon nanotubes reduced the anchoring density of ZnO nanoparticles, and the agglomerated ZnO exposed active sites decreased, leading to ZnO agglomeration. 2+ The release rate and antibacterial activity are reduced, the synergistic antibacterial effect with microcapsules is weakened, and it is difficult to form a dynamic antibacterial response.

[0036] Examples 5-7 The preparation method and parameters of Example 2 are similar, with specific differences shown in Table 3.

[0037] Comparative Example 4 The preparation method and parameters of Example 2 are the same, except that the glass fiber is not surface treated.

[0038] Comparative Example 5 The preparation method and parameters are the same as in Example 2, except that no surface-treated glass fibers are added.

[0039] Comparative Example 6 The preparation method and parameters were the same as in Example 2, except that short-cut carbon fibers were not added.

[0040] Experiment Example 2 Tensile properties were tested according to ISO 527; notched impact strength was tested according to ISO 179; flexural modulus was tested according to GB / T 9341-2008; the results are shown in Table 3.

[0041] Table 3 Mechanical property tests of Examples 2, 5-7 and Comparative Examples 4-6

[0042] As shown in Table 3, in Examples 2 and 5-7, the chopped carbon fibers and glass fibers treated with silane coupling agent KH550 significantly improved the fracture resistance of the material through a synergistic effect of "short-range and long-range". The high modulus of the chopped carbon fibers allows them to form micro-reinforcing points within the matrix, absorbing and dispersing local stress. Meanwhile, the high aspect ratio glass fibers, through the silane coupling agent and polypropylene compatibilizer, form a strong interfacial bond, exerting a "bridging" effect of continuous fibers and hindering crack propagation paths. The two types of fibers are uniformly distributed under the high-shear mixing of the extrusion process, forming a hierarchical network: carbon fibers primarily reinforce at the micron scale, while glass fibers dominate macroscopic stress bearing. This not only compensates for the interfacial weakness caused by single fibers but also optimizes stress distribution through the geometric differences of the fibers, ultimately improving the mechanical properties of the material. In Example 5, when the length of the short glass fibers was 3 mm, the length of the chopped carbon fibers was 100 μm, the amount of surface-treated glass fibers was 5 parts, and the amount of chopped carbon fibers was 3 parts, the resulting material exhibited the best mechanical properties, with a tensile strength of 34 MPa and a notched impact strength of 12.7 kJ / m. 2The flexural modulus was 1725 MPa. In Comparative Example 4, no surface treatment was applied to the glass fibers. The fiber surface was smooth and lacked active groups modified with silane coupling agents, resulting in a significant weakening of the physical anchoring and chemical bonding between the fibers and the matrix. Under stress, the fiber-resin interface was prone to debonding or slippage, failing to effectively transfer loads and reducing the fiber's reinforcing efficiency. In Comparative Example 5, no surface-treated glass fibers were added. The complete absence of glass fibers caused the material to lose its main reinforcing effect on the matrix, resulting in insufficient overall stiffness, a significant reduction in flexural modulus, and weakened stress dispersion ability, making it prone to brittle fracture under dynamic impact. Carbon fibers formed local high-modulus regions through random distribution, forming a "micro-nano synergy" with the three-dimensional network of bifunctional fillers and glass fibers. In Comparative Example 6, no short-cut carbon fibers were added, and the system lacked macroscopic fiber support. Relying solely on nanofillers may lead to uneven stress distribution, especially under high temperature or long-term load, exacerbating the tendency of molecular chain slippage.

[0043] Examples 8-10 The preparation method and parameters of Example 5 are as follows, with specific differences shown in Table 4; the ultrasonic time in Table 4 is the time for ultrasonication of boron nitride nanosheets added to sodium hydroxide solution.

[0044] Comparative Example 7 The preparation method and parameters of Example 5 were used, except that no compatibilizer was added.

[0045] Comparative Example 8 The preparation method and parameters of Example 5 were used, except that the compatibilizer was a styrene-maleic anhydride copolymer (purchased from Jinjinle Chemical Co., Ltd.).

[0046] Comparative Example 9 The preparation method and parameters of Example 5 were used, except that hydroxylated boron nitride nanosheets were not added.

[0047] Comparative Example 10 The preparation method and parameters of Example 5 were used, except that the boron nitride nanosheets were not modified by hydroxylation.

[0048] Experiment Example 3 Mechanical Property Testing Tensile properties were tested according to ISO 527; notched impact strength was tested according to ISO 179; the results are shown in Table 4 and... Figure 1 As shown.

[0049] Table 4 Mechanical property tests of Examples 5, 8-10 and Comparative Examples 7-10

[0050] From Table 4 and Figure 1As can be seen, in Examples 5 and 8-10, the molecular-level synergistic effect of hydroxylated boron nitride nanosheets (OH-BNNS) and maleic anhydride-grafted polypropylene (MAH-g-PP) significantly optimized the interfacial compatibility between the nanofiller and the polypropylene matrix. The active hydroxyl groups on the surface of OH-BNNS and the anhydride groups of MAH-g-PP are bonded through hydrogen bonds and even partial covalent bonds, which solves the aggregation problem caused by the high specific surface area of ​​BN sheets and ensures their uniform dispersion. The nanosheets are inserted into the gaps between polypropylene molecular chains, restricting chain segment movement and significantly improving the rigidity of the matrix. In the preparation process, the dual processes of alkali treatment and ultrasonic exfoliation of boron nitride achieve controllable sheet thickness, while freeze-drying locks in its monolayer dispersion state and avoids secondary aggregation. This linkage strategy of filler pretreatment and compatibilizer addition provides excellent rigidity support for the material. In Example 9, the material exhibited the best mechanical properties when the ultrasonic treatment time was 2.2 hours, the compatibilizer dosage was 1.5 parts, and the hydroxylated boron nitride nanosheet dosage was 2.5 parts, with a tensile strength of 37 MPa and a notched impact strength of 13.5 kJ / m. 2 In Comparative Example 7, the absence of a compatibilizer significantly reduced the interfacial affinity between the filler and the polypropylene matrix, disrupting the stress transfer path and increasing the risk of interfacial debonding. Especially under dynamic loads, cracks preferentially propagate along the filler-matrix interface, leading to a decrease in the material's mechanical properties. In Comparative Example 8, the compatibilizer was a styrene-maleic anhydride copolymer. While the maleic anhydride groups can improve interfacial polarity, the compatibility of its styrene segments with polypropylene is weaker than that of MAH-g-PP (polypropylene grafted with maleic anhydride), resulting in a decrease in molecular chain entanglement density and a reduction in interfacial transfer efficiency. Hydroxylated boron nitride nanosheets can physically intercalate to hinder matrix molecular chain slippage, improving material rigidity and inhibiting crack propagation through the lamellar "maze effect." In Comparative Example 9, the absence of hydroxylated boron nitride nanosheets caused the material to lose its unique two-dimensional lamellar reinforcement effect. In Comparative Example 10, the boron nitride nanosheets were not hydroxylated, resulting in strong surface inertness. They could not form hydrogen bonds or chemical bonds with the matrix or compatibilizer through hydroxyl groups, leading to poor dispersibility in polypropylene and easy agglomeration into micron-sized particles, causing stress concentration. The interfacial bonding force was weaker than that of the hydroxylated modified system, and the material rigidity and high-temperature dimensional stability deteriorated. The overall mechanical properties were even lower than those of the system without any added OH-BNNS.

[0051] Examples 11-13 The preparation method and parameters of Example 9 are as follows, with specific differences shown in Table 5; the ultrasonic time in Table 5 is ; the reaction time is .

[0052] Comparative Example 11 The preparation method and parameters were the same as in Example 9, except that antibacterial microcapsules were not added.

[0053] Comparative Example 12 The preparation method and parameters of Example 9 are the same, except that juniper alcohol was not added when preparing the antibacterial microcapsules.

[0054] Comparative Example 13 The preparation method and parameters of Example 9 are the same, except that nano-titanium dioxide was not added when preparing the antibacterial microcapsules.

[0055] Comparative Example 14 The preparation method and parameters of Example 9 are the same, except that cystamine was not added when preparing the antibacterial microcapsules.

[0056] Experiment Example 4: Antibacterial Performance Test Referring to the standard QB / T 2591-2003, Escherichia coli was selected as the test strain for antibacterial rate testing; the results are shown in Table 5.

[0057] Table 5 Antimicrobial performance tests of Examples 9, 11-13 and Comparative Examples 11-14

[0058] As shown in Table 5, in Examples 9 and 11-13, the antibacterial microcapsules, through the synergistic effect of a dual antibacterial mechanism and controlled-release process, endow the material with long-lasting antibacterial properties. The chitosan network of the shell can dynamically release hinoki alcohol in response to pH—in the weakly acidic environment produced by microbial metabolism, the chitosan segments swell and accelerate the release of active ingredients, and hinoki alcohol acts on the bacterial enzyme system to destroy its metabolic capacity, while the coated nano-TiO2 generates reactive oxygen species under light, achieving environmentally triggered sterilization; in the matrix, the polar chitosan of the microcapsule shell is partially exposed to the matrix surface through a compatibilizer, directionally enriching pathogenic bacteria, while the non-polar hinoki alcohol and TiO2 inside prolong the antibacterial period through a sustained-release mechanism. In Example 11, when the ultrasonic time was 20 min, the droplet size was 300 nm, the reaction time was 3.5 h, and the amount of antibacterial microcapsules was 8 parts, the material obtained had the best antibacterial performance, with an Escherichia coli inhibition rate of 99.9%. In Comparative Example 11, the absence of antibacterial microcapsules resulted in the material losing all active antibacterial functions. The material surface could not inhibit microbial attachment and proliferation through the slow-release of antibacterial components (such as juniper alcohol and nano-titanium dioxide reactive oxygen species), allowing bacteria / fungi to multiply freely and form biofilms. In Comparative Example 12, the absence of juniper alcohol in the preparation of antibacterial microcapsules caused the microcapsules to lose their core chemical bactericidal ability. Although the residual nano-titanium dioxide could generate reactive oxygen species (ROS) through photocatalysis, its effect was limited by light conditions and its antibacterial efficiency dropped sharply in the dark, resulting in a narrowed antibacterial spectrum and limited effectiveness. In Comparative Example 13, the absence of nano-titanium dioxide in the preparation of antibacterial microcapsules meant that the single chemical antibacterial mechanism relying on juniper alcohol was insufficient to cope with high concentrations of microorganisms or drug-resistant strains. Furthermore, the rapidly released juniper alcohol would be completely consumed, failing to achieve long-term antibacterial effects. The physical barrier function of the microcapsules was weakened due to the lack of TiO2 layered structure. Cystamine is used as a crosslinking agent or functional group modifier for the microcapsule shell. In Comparative Example 14, cystamine was not added when preparing antibacterial microcapsules. Its absence resulted in a loose shell structure and insufficient mechanical strength, causing uncontrolled leakage of internal antibacterial components (such as juniper alcohol, TiO2, etc.) (such as premature release or burst release).

[0059] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an antibacterial modified polypropylene material, characterized in that: The preparation method is as follows: polypropylene resin and compatibilizer are premixed to obtain mixture one; short-cut carbon fibers, bifunctional fillers, surface-treated glass fibers and hydroxylated boron nitride nanosheets are mixed and ball-milled to obtain mixture two; mixture one, mixture two and antibacterial microcapsules are added to a twin-screw extruder for melt blending, and then extruded and granulated to obtain the modified polypropylene material; The bifunctional filler is a carbon nanotube with ZnO nanoparticles grafted onto its surface. The surface-treated glass fiber is obtained by reacting a silane coupling agent with glass fiber. The hydroxylated boron nitride nanosheets were prepared by dispersing boron nitride nanosheets in a sodium hydroxide solution; The antibacterial microcapsules are chitosan encapsulated with juniper alcohol and loaded with nano-titanium dioxide.

2. The method for preparing an antibacterial modified polypropylene material according to claim 1, characterized in that: The melt index of the polypropylene resin is 10-30 g / 10 min.

3. The method for preparing an antibacterial modified polypropylene material according to claim 1, characterized in that: The preparation method of the bifunctional filler is as follows: the carbon nanotubes are immersed in acid and refluxed for 3-5.5 h; then washed until neutral, dispersed in ethanol, and 3-aminopropyltriethoxysilane is added to react and obtain aminated carbon nanotubes; the aminated carbon nanotubes are dispersed in deionized water, and 0.1-0.5 M zinc nitrate solution is added and stirred to react and generate ZnO nanoparticles; then polyvinylpyrrolidone is added and stirring is continued to obtain a reaction solution; the reaction solution is centrifuged, and the precipitate is washed and dried to obtain the bifunctional filler.

4. The method for preparing an antibacterial modified polypropylene material according to claim 1, characterized in that: The method for preparing the antibacterial microcapsules is as follows: Chitosan is added to glacial acetic acid and stirred to obtain a chitosan solution; Juniper alcohol and nano-titanium dioxide are mixed and added to anhydrous ethanol, and ultrasonically dispersed to obtain a dispersion; the chitosan solution is added and ultrasonically dispersed for 15-25 minutes to obtain a mixture; the mixture is dropped into liquid paraffin and sheared to form an oil-in-water emulsion; cystamine is added to the oil-in-water emulsion and stirred for 3-5 hours; sodium tripolyphosphate is added and stirred; then the mixture is centrifuged, washed, and dried to obtain the antibacterial microcapsules.

5. The method for preparing an antibacterial modified polypropylene material according to claim 4, characterized in that: The average droplet size of the oil-in-water emulsion is 200-500 nm.

6. The method for preparing an antibacterial modified polypropylene material according to claim 1, characterized in that: The length of the chopped carbon fibers is 50-200 μm.

7. The method for preparing an antibacterial modified polypropylene material according to claim 1, characterized in that: The surface-treated glass fiber is prepared as follows: the glass fiber is immersed in an ethanol solution containing the silane coupling agent, stirred, centrifuged and dried to obtain the surface-treated glass fiber; the glass fiber has a length of 1-5 mm.

8. The method for preparing an antibacterial modified polypropylene material according to claim 1, characterized in that: The method for preparing the hydroxylated boron nitride nanosheets is as follows: the boron nitride nanosheets are added to the sodium hydroxide solution, stirred, and then ultrasonically treated for 1.8-2.5 hours to obtain a suspension; the suspension is centrifuged, and the precipitate after centrifugation is placed in a refrigerator for pre-freezing, and then placed in a freeze dryer for drying to obtain the hydroxylated boron nitride nanosheets.

9. An antibacterial modified polypropylene material, characterized in that: The antibacterial modified polypropylene material is prepared by the preparation method described in any one of claims 1-8; the raw materials for producing the antibacterial modified polypropylene material include 85 parts of polypropylene resin, 1-5 parts of chopped carbon fibers, 3-8 parts of surface-treated glass fibers, 1-3 parts of hydroxylated boron nitride nanosheets, 5-15 parts of antibacterial microcapsules, 0.5-2 parts of compatibilizer and 3-8 parts of bifunctional filler.

Citation Information

Patent Citations

  • Preparation method of zinc oxide-carbon nanotube composite material

    CN107552035A

  • Preparation method of chitosan / sodium tripolyphosphate microsphere slow-release system with embedded GDNF (glial cell-derived neurotrophic factor)

    CN110251658A

  • Amphiphilic chitosan cystamine grafted derivative as well as preparation and application thereof

    CN116496430A

  • Easy-to-clean coating material and preparation method thereof

    CN119264710A

Cited By

  • Antibacterial mildew-proof polypropylene modified material and preparation method thereof

    CN121182066A

  • Antibacterial wood-plastic composite material for furniture customization and preparation method thereof

    CN121406055A